Informal workers' access to health care services: findings from a qualitative study in the Kassena-Nankana districts of Northern Ghana - James Akazili; Samuel Chatio; John Ele-Ojo Ataguba; Isaiah Agorinya; Edmund Wedam Kanmiki; Osman Sankoh; Abraham Oduro (BMC, 2018)
Abstract Background Over the past two decades, employment in the informal sector has grown rapidly in all regions including low and middle-income countries. In the developing countries, between 50 and 75% of workers are employed in the informal sector. In Ghana, more than 80% of the total working population is working in the informal sector. They are largely self-employed persons such as farmers, traders, food processors, artisans, craft-workers among others. The persistent problem in advancing efforts to address health vulnerabilities of informal workers is lack of systematic data. Therefore, this study explored factors affecting informal workers access to health care services in Northern Ghana. Method The study used qualitative methodology where focus group discussions and in-depth interviews were conducted. Purposive sampling technique was used to select participants for the interviews. The interviews were transcribed and coded into emergent themes using Nvivo 10 software before thematic content analysis. Results Study participants held the view that factors such as poverty, time spent at the health facility seeking for health care, unpleasant attitude of health providers towards clients affected their access to health care services. They perceived that poor organization and operations of the current health system and poor health care services provided under the national health insurance scheme affected access to health care services according to study participants. However, sale of assets, family support, borrowed money from friends and occasional employer support were the copying strategies used by informal workers to finance their health care needs. Conclusion Most of the population in Ghana are engaged in informal employment hence their contribution to the economy is very important. Therefore, efforts needed to be made by all stakeholders to address these challenges in order to help improve on access to health care services to all patients particularly the most vulnerable groups in society.